2016
DOI: 10.1097/j.pain.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Regular physical activity prevents chronic pain by altering resident muscle macrophage phenotype and increasing interleukin-10 in mice

Abstract: Regular physical activity in healthy individuals prevents development of chronic musculoskeletal pain; however, the mechanisms underlying this exercise-induced analgesia are not well understood. Interleukin-10(IL-10), an anti-inflammatory cytokine which can reduce nociceptor sensitization, increases during regular physical activity. Since macrophages play a major role in cytokine production and are present in muscle tissue, we propose that physical activity alters macrophage phenotype to increase IL-10 and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(164 citation statements)
references
References 71 publications
7
153
0
4
Order By: Relevance
“…A previous study demonstrated that 8 weeks of voluntary wheel running increases the ratio of gastrocnemius macrophages towards and M2 phenotype. 39 Therefore, we assessed the influence of prior running on macrophage phenotype in the sciatic nerve at 3 and 14 days after CCI. The expression of an M1 marker (iNOS) and an M2 marker (Arg-1) in the injured sciatic nerve were significantly increased at 3 and 14 days after CCI in the locked wheel controls ( P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that 8 weeks of voluntary wheel running increases the ratio of gastrocnemius macrophages towards and M2 phenotype. 39 Therefore, we assessed the influence of prior running on macrophage phenotype in the sciatic nerve at 3 and 14 days after CCI. The expression of an M1 marker (iNOS) and an M2 marker (Arg-1) in the injured sciatic nerve were significantly increased at 3 and 14 days after CCI in the locked wheel controls ( P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This difference may be attributed to alternative mechanisms between the CCI and intramuscular acidic saline models. For example, chronic pain induced by the latter is dependent on local pro-inflammatory signaling, 39,64 but unlike CCI, it is not dependent on spinal glia. 24,38 This suggests that the long-term protective effects of voluntary wheel running could be mediated by attenuation of central immune signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for macrophages was performed on cryopreserved sections of mouse muscle using rat monoclonal antibody recognizing F4/80 antigen (AbDSerotec, Raleigh, North Carolina), a glycoprotein expressed by mature murine macrophages using techniques we previously published [17;30]. Male and female C57BL/6J mice were anesthetized with an intraperitoneal injection of pentobarbital (50 mg/kg) and transcardially perfused with heparinized saline followed by either 1) 4% paraformaldehyde (clodronate quantification), or 2) PLP fixative (2% paraformaldehyde; 75mM Lysine; 10mM periodate; 0.05M Phosphate Buffer) (Fig.…”
Section: Immunohistochemistry Of Macrophages In Musclementioning
confidence: 99%
“…Similarly, M1 macrophages in the spinal cord contribute to chronic pain in rodent model of spinal cord injury (Willemen et al, 2012;Kigerl et al, 2009). Moreover, the induction of an M2 macrophage phenotype reverses or prevents the development of pain and inflammation in rodent models of paw incision and diabetes (Saito et al, 2015), acid-induced muscle pain (Leung et al, 2015), carrageenan-induced inflammation (Willemen et al, 2012) or spinal cord injury (Willemen et al, 2012;Kigerl et al, 2009). In humans (Brueckmann et al, 2004) and mice (Khallou-Laschet et al, 2010), the extended presence of M1 macrophages and a systemic inflammatory response are associated with the development of atherosclerosis and acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 98%
“…An abnormally prolonged M1 phenotype in macrophages may result in chronic inflammatory processes found in conditions such as chronic pain, atherosclerosis, obesity, etc. Recent studies have shown peripheral (muscle) M1 macrophages are associated in prolonged hyperalgesia in mice (Leung et al, 2015). Similarly, M1 macrophages in the spinal cord contribute to chronic pain in rodent model of spinal cord injury (Willemen et al, 2012;Kigerl et al, 2009).…”
Section: Introductionmentioning
confidence: 99%